Tribute to Juan Aste Daffós - Alfaro Montoya, Kely (2025)
Juan Aste Daffós, a graduate of our university (code 1969), was an economist engineer committed to the country, to people's rights and the defense of nature. In his professional career, he was an advisor to trade unions, peasant communities, indigenous communities, farmers' associations, association of territorial defenders, among others; researcher, activist and, above all, a person committed to his ideals. He was one of those people who made his life a single line of coherence: between knowledge and action, between technique and tenderness, between rigor and joy. His legacy is not enclosed in his books, nor in his reports, nor even in the laws he helped to draft: his legacy is alive in every person, community and movement that today continues to fight for an economy for life, for a collective, communitarian and just society and for pollution-free territories.